Inherited ichthyosis: Non‐syndromic forms. Issue 3 (March 2016) - Takeichi, Takuya; Akiyama, Masashi
Abstract: Inherited ichthyoses are a group of genetic disorders characterized by generalized dry skin, scaling and hyperkeratosis, and often associated with erythroderma. These manifestations are due to mutations in genes mostly involved in skin barrier formation. Inherited ichthyoses consist of non‐syndromic ichthyoses and ichthyosis syndromes. Non‐syndromic ichthyoses are characterized by the phenotypic expression of the disorder being seen only in the skin. Non‐syndromic ichthyoses include ichthyosis vulgaris, recessive X‐linked ichthyosis, autosomal recessive congenital ichthyosis, keratinopathic ichthyosis and other forms. This review focuses on updates for each type of non‐syndromic ichthyosis, highlighting molecular mechanisms and phenotype/genotype correlations. Included in autosomal recessive congenital ichthyosis are three of the major phenotypes (harlequin ichthyosis, lamellar ichthyosis and congenital ichthyosiform erythroderma) and three of the minor subtypes (self‐healing collodion baby, acral self‐healing collodion baby and bathing suit ichthyosis). Keratinopathic ichthyosis is proposed as an umbrella term for ichthyoses caused by mutations in keratin genes. Next‐generation sequencing technologies have become powerful tools for the diagnosis of inherited ichthyoses and the discovery of their genetic causes. This article reviews the current understanding of molecular pathomechanisms for non‐syndromic ichthyoses and explores future perspectives.